Innovation in English Gothic Architecture: Risks, Impediments, and Opportunities - Paul Binski (British Art Studies, 2017)
Medieval invention is considered first in relation to the powers of the rational and the irrational: the outcome of an artefact may have particular persuasive (more rarely supernatural) force which casts light on the makers of the artefact themselves. Was especially remarkable art necessarily the product of virtue? The answer in Antiquity and the medieval world was clearly “no”. The rational and rhetorical idea of persuasion touched and blurred with the idea of seduction, and the agency in the making of an artefact might appear supernatural, free of human agency. But exceptional effects are not norms, and the concern of this paper is with the everyday, the social, rather than the exceptional and unique. This is explored in the second half by thinking about rules and conventions that are agreed socially, and in regard to which the aesthetic and the ethical once more touch and blur. Stress is laid on the medieval pleasures of taking conventions and playing with them in the process of art realization, a social process which could ultimately reaffirm the authority of traditional starting points.